Analisis Dampak Pembiasaan Berdoa Bersama terhadap Peningkatan Kedisiplinan Siswa di Kelas III SD Negri 2 Bakan - Erna Sudariah (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study aims to analyze the impact of the routine practice of communal prayer on improving student discipline in the third grade at SD Negeri 2 Bakan. The research employs a qualitative descriptive approach with a case study methodology. Data was collected through a systematic search and analysis of academic documents, including scientific journals, books, and conference proceedings from databases like Google Scholar, focusing on keywords such as